2021
DOI: 10.2147/dmso.s298185
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA LINC00673 is Downregulated in Diabetic Retinopathy and Regulates the Apoptosis of Retinal Pigment Epithelial Cells via Negatively Regulating p53

Abstract: Background: Long noncoding RNA (LncRNA) LINC00673 has been proven to play critical roles in cancer biology, while its role in other diseases is unknown. It has been reported that LINC00673 could interact with p53, a critical player in diabetes and diabetic complications, suggesting that LINC00673 may also participate in diabetic retinopathy (DR). This study aimed to investigate the role of LINC00673 in DR. Methods: The present study included 3 groups of participants, including DR group, diabetes (DB) group, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Studies that have discussed the possible correlation between LINC00673 SNP and DR development are rare; only one study has evaluated the relationship between LINC00673 expression and DR ( Cheng et al, 2021 ). In our study, the frequency of LINC00673 SNPs (i.e., rs6501551, rs9914618, and rs11655237) was not significantly different between the non-DR and DR groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that have discussed the possible correlation between LINC00673 SNP and DR development are rare; only one study has evaluated the relationship between LINC00673 expression and DR ( Cheng et al, 2021 ). In our study, the frequency of LINC00673 SNPs (i.e., rs6501551, rs9914618, and rs11655237) was not significantly different between the non-DR and DR groups.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, research on the relationship between the SNPs of LINC00673 and DR development is rare. Because LINC00673 is downregulated in patients with DR ( Cheng et al, 2021 ), the SNPs of LINC00673 may also affect the clinical features of DR.…”
Section: Introductionmentioning
confidence: 99%
“…lncRNA H19 reduces inflammation by inhibiting miR-93 expression via XBP1s in HG-induced RPE cells [ 128 ]. Overexpression of lncRNA LINC00673 can downregulate the expression of p53, thereby inhibiting the apoptosis of RPE cells in HG conditions [ 129 ]. lncRNA AK077216 reduces ARPE-19 cell apoptosis by inhibiting the expression of miR-383 [ 130 ].…”
Section: Incrnasmentioning
confidence: 99%
“…Additionally, in a recent paper it has been observed that Mini-chromosome Maintenance Complex Component 3 Associated Protein Antisense ( MCM3AP-AS1 ) was downregulated in DR patients comparing to T2D subjects and promotes cell apoptosis by regulating miR-211/ SIRT1 axis [ 174 ]. Moreover, the downregulation of the Long Intergenic Non-Coding RNA 673 ( LINC00673 ) has been reported in plasma samples of DR patients [ 175 ]. Interestingly, LINC00673 induces apoptosis in retinal pigment epithelial cells (RPECs) under HG conditions by negatively regulating p53.…”
Section: Long Non-coding Rnas With Reduced Expression In Diabetic Ret...mentioning
confidence: 99%
“…Interestingly, LINC00673 induces apoptosis in retinal pigment epithelial cells (RPECs) under HG conditions by negatively regulating p53. [ 175 ]. Interestingly, in a recent work from Sehgal and colleagues, the Vascular Endothelial-Associated LncRNA 2 ( VEAL2 ) has been identified as a novel lncRNA implicated in human vascular disease [ 176 ].…”
Section: Long Non-coding Rnas With Reduced Expression In Diabetic Ret...mentioning
confidence: 99%